2018
DOI: 10.2147/cmar.s181910
|View full text |Cite
|
Sign up to set email alerts
|

Low STYK1 expression indicates poor prognosis in gastric cancer

Abstract: BackgroundThe expression of serine threonine tyrosine kinase 1 (STYK1), a member of the receptor protein tyrosine kinase (RPTK) family, is abnormal in several cancers. However, the molecular mechanism of STYK1 regulation of gastric cancer (GC) progression is unknown.Materials and methodsWe evaluated STYK1 expression in GC tissues and the corresponding normal tissues. Specimens from 93 patients with GC were examined with immunohistochemical staining. The relationship between STYK1 protein expression and the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Our results confirmed that STYK1 was overexpressed in NSCLC, indicating that STYK1 could play a significant role in NSCLC progression. This tendency is consistent with STYK1 overexpression in many other malignancies ( Moriai et al, 2006 ; Jackson et al, 2009 ; Kondoh et al, 2009 ; Orang et al, 2014 ; Chen et al, 2016 , 2017 ; Hu et al, 2018 ), except for gastric cancer ( Fang et al, 2018 ) and some cases of castration-naïve prostate cancer ( Chung et al, 2009 ). In addition, in vitro and in vivo experiments demonstrated that the upregulation of STYK1 expression caused epithelial NSCLC cells to acquire mesenchymal features, to migrate, and to invade, which suggests that STYK1 facilitates metastasis of NSCLC cells to distant sites.…”
Section: Discussionsupporting
confidence: 81%
“…Our results confirmed that STYK1 was overexpressed in NSCLC, indicating that STYK1 could play a significant role in NSCLC progression. This tendency is consistent with STYK1 overexpression in many other malignancies ( Moriai et al, 2006 ; Jackson et al, 2009 ; Kondoh et al, 2009 ; Orang et al, 2014 ; Chen et al, 2016 , 2017 ; Hu et al, 2018 ), except for gastric cancer ( Fang et al, 2018 ) and some cases of castration-naïve prostate cancer ( Chung et al, 2009 ). In addition, in vitro and in vivo experiments demonstrated that the upregulation of STYK1 expression caused epithelial NSCLC cells to acquire mesenchymal features, to migrate, and to invade, which suggests that STYK1 facilitates metastasis of NSCLC cells to distant sites.…”
Section: Discussionsupporting
confidence: 81%
“…IHC was performed as describe previously ( 16 ). Briefly, the tissues were exposed to primary antibodies like macrophage inflammatory protein-1α (CCL3; 1:200, DF8572, Affinity), MMP3 Monoclonal antibody (1:200, 66338-1-Ig, Proteintech), and TIMP1 polyclonal antibody (1:200, 16644-1-AP, Proteintech).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described previously ( 16 ). The membranes/blot were incubated with primary antibodies like CCL3, MMP3, TIMP1, and GAPDH (CCL3; 1:1000, DF8572, Affinity; MMP3 Monoclonal antibody, 1:5000, 66338-1-Ig, Proteintech; TIMP1 polyclonal antibody, 1:1000, 16644-1-AP, Proteintech; GAPDH, 1:20000, 60004-1-Ig, Proteintech; Rainbow 180 plus Marker, 39.VPM003, VICMED; Universal antibody diluent, 39.VP6022-50, VICMED).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedures for the immunohistochemical experiments are described above (20), the tissue section was treated with primary antibodies against TIMP2 (sc-21735, working dilution 1: 50, Santa Cruz Biotechnology, Inc., USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%